Immunohistochemical analysis of CD34 and PCNA expression in salivary and laryngeal adenoid cystic carcinoma - El-Azab, Samia; Alqalshy, Emad; El-Rahman, Kamal Abd; Hussein, Ahmed; Ibrahim, Amr; Alazzazi, Magdy Alabasiry; Abdel-Wahab, Amr Saad; Mahmoud, Hany Mahmoud; Abdelhameed, Wael Badawy; Esmail, Abd Elnasser Abd El Mola (International journal of health sciences, 2021)
Background/purpose: Adenoid cystic carcinomas (ACC) are malignant tumors that affect major and minor salivary glands. LACC is an extremely rare location for this type of tumour. This study describes the immunohistochemical analysis of CD34 and PCNA expression in salivary and laryngeal ACC. Materials and methods: The study included 40 formalin-fixed paraffin-embedded blocks were used, 20 of them were previously diagnosed as SACC, and 20 as LACC. All sections were stained with hematoxylin and eosin (H&E) and immunohistochemical marker to detect CD34 and PCNA protein. Results: Regarding the expression of CD34, SACC had recorded the highest mean area % (31.58), while LACC recorded the lowest mean area % (14.25) and the comparison revealed that there was a highly significant difference between these lesions where P value was (<0.001) concerning the expression of PCNA, SACC had recorded the highest mean area % (36.28), while LACC recorded the lowest mean area % (20.7) and the comparison revealed that there was a highly significant difference between these lesions where P value was (<0.001). Conclusions: immunohistochemical analyses presented here indicated that LACC tends to nonaggressive oncological behavior and angiogenesis when compared to SACC.